Memory and functional brain differences in a national sample of U.S. veterans with Gulf War Illness. (30th April 2016) - Cooper, Crystal M.; Briggs, Richard W.; Farris, Emily A.; Bartlett, James; Haley, Robert W.; Odegard, Timothy N.
Abstract: Roughly 26–32% of U. S. veterans who served in the 1991 Persian Gulf War report suffering from chronic health problems. Memory complaints are regularly reported by ill Gulf War veterans (GWV), but limited data verify their complaints. This study investigated episodic memory and brain function in a nationally representative sample of GWV, using a face-name memory task and functional magnetic resonance imaging during encoding. A syndrome classification system was used to subdivide ill GWV into the three major Gulf War Illness syndrome types, "impaired cognition" (GWV-1), "confusion ataxia" (GWV-2), and "central pain" (GWV-3). Memory and brain function of ill GWV were contrasted to deployed and nondeployed well GWV controls (GWV-C). Ill GWV exhibited impaired memory function relative to GWV-C but the patterns of functional brain differences varied. Brain activation differentiated the GWV-C from the ill GWV. The different syndrome types also differed from one another in several brain regions. Additionally, the current study was the first to observe differences in brain function between deployed and nondeployed GWV-C. These results provide (1) evidence of memory impairment in ill GWV and differentiate the syndrome types at a functional neurobiological level, and (2) the role of deployment in the war on brain function. Highlights: Memory complaints of ill Gulf War Veterans confirmed with an objective memory task. Brain activation during the memory task differentiated the ill GWV syndrome types. Deployed and non-deployed veterans had different brain responses to the memory task.